Report of findings from a review of the operation of the National Livestock Identification System - PricewaterhouseCoopers (Australia); Australia. Department of Agriculture, Fisheries and Forestry (Barton, A.C.T. : Dept. of Agriculture, Fisheries and Forestry, 2006)
The National Livestock Identification Scheme (NLIS) is Australia's system for identifying and tracking all cattle through their life. It is a permanent, whole-of-life identification system which aims to ensure that individual animals can be tracked from property of birth to slaughter for bio-security, food safety, and product integrity and market access purposes.
"December 2006".
Title from title screen (viewed on 11 October 2007).
Text and graphics.
Mode of access: Internet via World Wide Web. Available at: http://www.daffa.gov.au/__data/assets/pdf_file/117325/nlis-report.pdf
System requirements: Adobe Acrobat reader required to view/print pdf files.
Selected for archiving
Keywords: National Livestock Identification Scheme (Australia); Cattle -- Australia -- Identification; Livestock -- Australia -- Identification -- Data processing